Pilot outcomes and exploration of treatment mechanisms using a culturally adapted version of the unified protocol for transdiagnostic treatment of emotional disorders to improve mental health symptoms, alcohol misuse, functional outcomes, and sleep quality in emergency responders - Meyer, Eric C.; Roth, Sheila G.; Coe, Elizabeth; Taylor, Daniel J.; Gulliver, Suzy B. (Frontiers in Health Services, 2025)
IntroductionEmergency responders encounter frequent trauma and myriad occupational hazards, contributing to concerning rates of posttraumatic stress disorder (PTSD) and related mental health symptoms. These symptoms are each strongly linked with neuroticism/negative emotionality (NNE). Thus, an emotion-focused, transdiagnostic, skills-based treatment approach seems to be a strong match for this population. We sought to address barriers to mental health treatment for emergency responders, including stigma, logistical barriers, and lack of provider knowledge regarding emergency response culture by delivering treatment via telehealth by providers trained in emergency response culture.MethodsIn an uncontrolled pilot trial, we delivered the Unified Protocol for Transdiagnostic Treatment of Emotional Disorders to 30 emergency medical service, police, and fire service personnel.ResultsThe large majority (80.0%) completed treatment. Working Alliance Inventory scores were high. Large improvements occurred at post-treatment and one-month follow-up in PTSD symptom severity (Hedges' g = 1.1 at post-treatment; g = 1.3 at follow-up), depression (g = 1.3; 1.3), anxiety (g = 1.1; 1.0), functional impairment (g = 1.2; 1.1), and quality of life (g = .89; .81). Small-to-medium sized improvements occurred in sleep quality (g = .42; .69) and engagement in values-consistent behavior (g = .34; .77). There were large, theory-consistent improvements during treatment in NNE (g = 1.1), difficulties in emotion regulation (g = .94), and experiential avoidance (g = 1.1), and large associations between changes in these mechanistic variables and improved treatment outcomes.DiscussionWe summarize our cultural adaptation process aimed at maximizing fit of the UP with emergency responders and recommend additional, controlled research examining the UP in trauma exposed populations. Clinical Trial RegistrationNCT05357586.